The Properties of the Chlorophyll a/b-Binding Proteins Lhca2 and Lhca3 Studied in Vivo Using Antisense Inhibition - Ganeteg, Ulrika (American Society of Plant Physiologists, 2001)
The specific functions of the light-harvesting proteins Lhca2 and Lhca3 were studied in Arabidopsis ecotype Colombia antisense plants in which the proteins were individually repressed. The antisense effect was specific in each plant, but levels of Lhca proteins other than the targeted products were also affected. The contents of Lhca1 and Lhca4 were unaffected, but Lhca3 (in Lhca2-repressed plants) was almost completely depleted, and Lhca2 decreased to about 30% of wild-type levels in Lhca3-repressed plants. This suggests that the Lhca2 and Lhca3 proteins are in physical contact with each other and that they require each other for stability. Photosystem I fluorescence at 730 nm is thought to emanate from pigments bound to Lhca1 and Lhca4. However, fluorescence emission and excitation spectra suggest that Lhca2 and Lhca3, which fluoresce in vitro at 680 nm, also could contribute to far-red fluorescence in vivo. Spectral forms with absorption maxima at 695 and 715 nm, apparently with emission maxima at 702 and 735 nm, respectively, might be associated with Lhca2 and Lhca3.